A Path Forward for Advancing Nonprofit Ethics and Accountability: Voices from an Independent Sector Study (Journal of Public and Nonprofit Affairs, 2020)
The nonprofit sector continues to grow in size, assets, and influence. However, a critical eye in recent years has brought scrutiny from many stakeholders to the operations of nonprofit organizations (NPOs). Accountability, transparency, and ethical behavior are now part of the everyday language of NPO leaders, staff, volunteers, donors, and board members. This study synthesizes research on a specific set of guidelines developed by Independent Sector and provides a substantive review of key concepts and developments related to nonprofit ethics and accountability. The results should prove useful for NPO staff, stakeholders, regulators, the media, and others interested in improved governance.